Growing Up in (and Out of) Shenzhen: The Longer-Term Impacts of Rural-Urban Migration on Education and Labor Market Entry. - Goodburn, Charlotte (China Journal, 2020)
Extensive research has shown that rural-to-urban migrant children in China face significant barriers to an urban public primary school education and often end up in poor-quality, migrant-run private schools. However, much less is known about what happens after children leave junior high school. This article therefore draws on two rounds of interviews with migrant children educated in Shenzhen, in 2008–9 and then in 2015–16, to examine in detail their experiences of schooling and labor-market entry. It identifies four distinct pathways of education—state vocational school, private migrant secondary school, state academic high school, and return to the countryside for further schooling—and suggests that these educational routes all ultimately lead to the same endpoint: regardless of pathway, aptitude, financial investment in education, and earlier career aspirations, migrant youths are channeled into low-skilled urban service work. This is in marked contrast to the hopes of parents that their children will achieve upward mobility through investment in education. This article analyzes the multiple reasons for the depressing uniformity of outcomes and the crucial role of state policy at both the central and local levels in perpetuating migrant disadvantage.